MANAJEMEN PEMBELAJARAN KARAKTER ANAK USIA DINI DI RA WADAS KELIR - Siti Zubaedah; Yoyon Suryono; Puji Yanti Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
Regulations for a learning activity, both learning activities that are categorized in the core curriculum or supporting curriculum based on the previously determined curriculum by the Ministry of National Education or the Ministry of Religion. Learning management provides a concept in superior learning performance, this is superior because there must be a scope in the learning process, namely teachers, principals, students, and parents to work together in supporting good character learning. This study uses a qualitative description by looking at the field. The researcher collected the data using interviews and observations with the class teacher and some of the students involved. The place of his research is Raudhatul Athfal Wadas Kelir Purwokerto Selatan, in this character learning process using management results through, (1) Orientation of Early Childhood Character Learning, (2) Orientation of Results of Early Childhood Character Learning, (3) Children's Character Learning Tools, ( 4) Children's Character Learning Performance. These four character learning management will be oriented towards an attachment of superior and useful character values to the management of learning in their institutions